Radiography of an educational institution: the Normal School of Cosenza from birth to the Great War - Trebisacce, Nicola (Rivista di Storia dell’Educazione, 2022)
The article reconstructs the history of the Scuola Normale of Cosenza from its birth, after the constitution of the Kingdom of Italy, until the eve of the Great War. In more than half a century the School, despite its logistical, economic and organizational difficulties, has played an important role in the training of teachers who have contributed to the dissemination of education and the growth, not free from contradictions and limits, of Calabrian and Southern society.